Manajemen Pakan dan Analisis Profitabilitas Usaha Peternakan Sapi Potong Rakyat di Masa Pandemi Covid 19 di Kabupaten Langkat - Ruth Dameria Haloho; Elvany Tarigan (Fakultas Pertanian, Universitas Timor, 2021)
The purpose of this study is to determine the feed management and profitability of smallholder beef cattle farming. The study was conducted in Langkat Regency with a total of 80 respondents from smallholder beef cattle business. The method of the study is a survey. The data analysis used is descriptive quantitative. Data were analyzed using income analysis, profitability and One Sample T-Test using SPSS. The results showed that the management of feed, namely the feed provided only consisted of forage, feeding was given in the morning and evening and the way of feeding was the Kreman method. Based on the results of calculations during the covid 19 pandemic, the total of revenue were Rp. 16,122,500; production cost of Rp. 12,389,581. The amount of income is Rp. 3,732,919. Profitability value of 23.15% is greater than BRI Bank deposits of 4%, so the beef cattle business is declared profitable and feasible to be developed.